Corporate culture and CEO turnover - Fiordelisi, Franco; Ricci, Ornella (Journal of Corporate Finance, 2014)
We study the effect of corporate culture on the relationship between firm performance and CEO turnover. Utilising a measure of cultural dimension developed in organisation behaviour research, we quantify corporate culture by assessing official documents using a text analysis approach. We employ this quantification to examine the impact of culture on CEO turnover, especially in the case of poor firm-specific performance. First, we find strong evidence of a negative relationship between firm-specific performance and CEO turnover. Second, we demonstrate that the probability of a CEO change, on average, is positively influenced by the competition- and creation-oriented cultures. The negative relationship between firm-specific performance and CEO turnover is reinforced by the control-oriented culture and reduced by the creation-oriented culture. Finally, we study the CEO insider or outsider succession and observe that the creation-oriented culture has a negative relationship with the probability of hiring an outsider. Moreover, the creation-oriented culture weakens the negative relationship existing between the firm-specific performance under the incumbent CEO and the probability of hiring an outsider.